1999
DOI: 10.1212/wnl.53.5.946
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of risperidone, placebo, and haloperidol for behavioral symptoms of dementia

Abstract: Low-dose risperidone (mean 1.1 mg/d) was well tolerated and associated with reductions in the severity and frequency of behavioral symptoms, particularly aggression, in elderly patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
388
2
15

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(416 citation statements)
references
References 26 publications
11
388
2
15
Order By: Relevance
“…In another meta-analysis, Lonergan et al (2001) found that haloperidol was beneficial for dementia patients with aggression, but not for general agitation (ie wandering, verbal agitation, etc). Similarly, in recent trials, no significant therapeutic effects were found for haloperidol compared with placebo and trazodone (Teri et al, 2000), compared with placebo and quetiapine (Tariot et al, 2006), and compared with risperidone and placebo (De Deyn et al, 1999). Some, although not all, RCTs with risperidone, olanzapine, and aripiprazole have shown modest efficacy for reducing aggression and overall agitation in AD (Ballard and Waite, 2006;Sink et al, 2005).…”
Section: Agitationmentioning
confidence: 95%
See 1 more Smart Citation
“…In another meta-analysis, Lonergan et al (2001) found that haloperidol was beneficial for dementia patients with aggression, but not for general agitation (ie wandering, verbal agitation, etc). Similarly, in recent trials, no significant therapeutic effects were found for haloperidol compared with placebo and trazodone (Teri et al, 2000), compared with placebo and quetiapine (Tariot et al, 2006), and compared with risperidone and placebo (De Deyn et al, 1999). Some, although not all, RCTs with risperidone, olanzapine, and aripiprazole have shown modest efficacy for reducing aggression and overall agitation in AD (Ballard and Waite, 2006;Sink et al, 2005).…”
Section: Agitationmentioning
confidence: 95%
“…However, there have been only four RCTs comparing these two classes of antipsychotics in persons with dementia: three comparing risperidone with haloperidol (Chan et al, 2001;De Deyn et al, 1999;Suh et al, 2004), and one comparing quetiapine and haloperidol (Tariot et al, 2006). Only one of the four trials found a significantly greater efficacy with the atypical than with the typical agent; the others found no significant difference in this respect.…”
Section: Comparisons With Typical Antipsychoticsmentioning
confidence: 99%
“…This might have been expected, as the efficacy of antipsychotic drug treatment, compared to a placebo, for these behavioral disturbances has been proved (Brodaty et al, 2003;De Deyn et al, 1999). The effectiveness of antipsychotic drugs in dementia is, however, modest (Gormley and Howard, 1999).…”
Section: A N T I P S Y C H O T I C S a N T I P S Y C H O T I C S N O mentioning
confidence: 99%
“…The introduction of atypical antipsychotics, such as risperidone and olanzapine, has changed the treatment for this population, as they are more effective in controlling BPSD and have fewer and milder extrapyramidal side-effects (EPS) than conventional antipsychotics (Brodaty et al, 2003;De Deyn et al, 1999). In the USA the atypical antipsychotics have now become a more common treatment for old people with dementia than the conventional drugs (Liperoti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lorazepam is commonly used for treatment of acute agitation, and the benzodiazepines are currently among the few agents available in a parenteral formulation for treatment of agitation. Use of orally administered atypical antipsychotics such as olanzapine and risperidone has met with some success in treating behavioral disturbances in patients with dementia (Clark et al 2001;De Deyn et al 1999;Katz et al 1999;Street et al 2000). A parenteral formulation of a second-generation antipsychotic might offer some advantage over their corresponding oral formulations due to faster onset of effect and utility where the patient cannot, or will not, accept oral treatment (Bianchetti et al 1980;Schaffer et al 1982).…”
mentioning
confidence: 99%